Early‐ and late‐onset posttransplant lymphoproliferative disorders among adult kidney and liver transplant recipients. (14th July 2022) - Abdulovski, Ranya; Møller, Dina L.; Knudsen, Andreas D.; Sørensen, Søren S.; Rasmussen, Allan; Nielsen, Susanne D.; Wareham, Neval E.
Abstract: Objectives: Posttransplant lymphoproliferative disorder (PTLD) in solid organ transplant recipients has a high mortality and may present early (<2 years) or late (≥2 years) posttransplantation. We investigated the clinical characteristics of early and late PTLD among kidney and liver transplant recipients. Methods: Recipients, transplanted at Rigshospitalet, with PTLD development as adults from January 2010 to August 2020, were included. Clinical characteristics, laboratory parameters, and pathology of early and late PTLD were compared. Results: Thirty‐one PTLD cases were detected where 10 (32%) were early and 21 (68%) were late PTLD. EBV DNA in plasma was detected in 78% versus 28% in early and late PTLD ( p  = .037). None of the recipients with early PTLD and nine recipients with late PTLD (47%) had Ann Arbor stage IV at the time of their diagnosis ( p  = .006). Cyclophosphamid–Hydroxyrubicin–Oncovin–Prednisolon was used for treatment in 10 (48%) recipients with late PTLD ( p  = 0.032) only. There was no difference in mortality between the two groups. Conclusions: Recipients with late PTLD had a lower prevalence of detectable EBV DNA in plasma, were diagnosed with more advanced disease, and were more frequently treated with chemotherapy compared to recipients with early PTLD.